Health on equal terms? - Västra Götaland, 2010 - Health on equal terms, Västra Götaland - 2010 - Public Health Agency of Sweden (City of Gothenburg, 2015)
The survey “Health on equal terms?” is a national survey, conducted every year since 2004. The Public Health Agency is responsible for the survey and Statistics Sweden (SCB) is responsible for the distribution, collection and registration. During the data collection in 2010, the City of Gothenburg ordered an additional sample for Gothenburg.

The additional sample in 2010 included all individuals aged 16-84 years living in Gothenburg. The questionnaire were answered by 3,014 individuals from the sample in Gothenburg, representing a response rate of 45 percent.

Including the national sample produced by Statistics Sweden (SCB), a total of 4,211 individuals participated from Västra Götaland County.

The questionnaire was printed in two versions. Addition to the national public health questionnaire, a similar questionnaire was conducted including the EQ-5D instrument. The questionnaire with the EQ-5D instrument was sent to the additional sample in Gothenburg. The questionnaire with the EQ-5D instrument consisted of 143 questions covering e.g. issues of health, lifestyle, economic conditions, work and employment, and security and social relations. In addition to data collected through the questionnaires, registry data were also included.

Purpose:

The aim of the national survey was to investigate the health in the population and to show changes in the population's health over time as a follow up of the national health politics. The aim of the additional sample in Gothenburg was to investigate the health in the population living in Gothenburg.

Undersökningen ”Hälsa på lika villkor?” är en stor nationell undersökning som genomförts varje år sedan 2004. Folkhälsomyndigheten ansvarar för undersökningen medan Statistiska centralbyrån (SCB) ansvarar för utskick, insamling och registrering av svar. I samband med undersökningen 2010 beställde Göteborgs Stad ett tilläggsurval för Göteborg.

Tilläggsurvalet för 2010 års undersökning inkluderade invånare 16-84 år i Göteborgs Stad. Frågeformuläret besvarades av totalt 3014 individer från tilläggsurvalet, vilket motsvarade en svarsfrekvens på ca 45 procent.

Antal svar för hela Västra Götalands län, d.v.s inklusive det nationella urvalet som tagits fram av Statistiska centralbyrån (SCB), uppgick till totalt 4211 individer.

Det trycktes två olika versioner av frågeblanketten, dels den nationella frågeblanketten och dels en variant som innehöll nästan alla frågor i den nationella blanketten samt frågeinstrumentet EQ5D. Göteborgs stad valde att deras tilläggsurval skulle få EQ5D-blanketten. EQ5D-blanketten bestod av 81 numrerade frågor varav flera hade delfrågor, vilket genererade totalt 143 frågor. Frågorna handlade bl.a. om hälsa, levnadsvanor, ekonomiska förhållanden, arbete och sysselsättning samt trygghet och sociala relationer. Förutom variabler som samlats in via frågeblanketten har ett antal registervariabler hämtats från SCB:s Registret över totalbefolkningen (RTB), utbildningsregistret, inkomst- och taxeringsregistret samt Geodatabasen.

Syfte:

Syftet med den nationella undersökningen var att ta reda på hur Sveriges befolkning mår och lever. Syftet med tilläggsurvalet var att ta reda på hur befolkningen i Göteborg mår och lever.
Hälsa på lika villkor? - Västra Götaland, 2010 - Hälsa på lika villkor, Västra Götaland - 2010
Keywords: Health Services; Hälso- och sjukvård; Physical Examination; Hälsokontroll; Dental Care; Tandvård; Hearing; Hörsel; Life Style; Livsstil; Medicine; Medicin; Exercise; Träning; Population Surveillance; Populationsövervakning; Hearing Loss; Hörselnedsättning; Socioeconomic Factors; Socioekonomiska faktorer; Tinnitus; Öronsusning; Urinary Incontinence; Urininkontinens; Anxiety; Ångest; Overweight; Övervikt; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Work; Arbete; Asthma; Astma; Diabetes Mellitus; Diabetes; Eczema; Eksem; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Headache; Huvudvärk; Health; Hälsa; Health Status; Hälsotillstånd; Hypertension; Högt blodtryck; Body Weight; Kroppsvikt; Drug Utilization; Läkemedelsförsörjning; Gastrointestinal Diseases; Mag-tarmsjukdomar; Migraine Disorders; Migränsjukdomar; Oral Health; Munhälsa; Depression; Depression; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Registries; Register; Smoking; Rökning; Disease; Sjukdom; Pain; Smärta; Tobacco, Smokeless; Rökfri tobak; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Vision, Ocular; Syn; Sleep; Sömn; Sleep Wake Disorders; Sömn- och vakenhetsstörningar; Fatigue; Trötthet; Occupations; Yrken; Occupational Exposure; Yrkesmässig exponering; Hypersensitivity; Överkänslighet; Feeding Behavior; Ätbeteende